The Mechanical Analysis of ELM Joint under Coupling Field - Wang, Xianewei; Chen, Xiuxiang; Han, Peng; Jiang, Qinxian; Li, Xiulian (Manufacturing Technology Journal, 2022)
The Edge Localized Mode coil is the key component to prohibit the phenomena of disruptive instability occur-ring in the edge of Tokamak plasma. And the coil is made of Stainless Steel Jacketed Mineral Insulated Con-ductors. The different pieces of conductor are connected by joints. During the normal operation of Tokamak device, the joint will be shocked by electromagnetic and thermal loads. Thus, it is necessary to perform the mechanical analysis to verify whether or not the ELM joint has sufficient safety margin to resist the impact of coupling field. In order to obtain the load boundary condition for mechanical analysis, the electromagnetic and thermal analysis are launched first. Then the temperature and electromagnetic force density are inserted into the mechanical analysis model. And the equivalent stress is calculated. The analysis results indicate there is stress intensity at the component of supporting rail. To mitigate the stress intensity, the local structural optimi-zation design is employed. Finally, the stress evaluation is carried out based on analytical design. The assess-ment results demonstrate the optimized model has sufficient safety margin to withstand the combined action of multiple loads.
Keywords: ELM joint; Electromagnetic force; thermal load; Stress evaluation